Bereavement support with the use of artificial intelligence – a quasi-systematic review - Bork-Zalewska, Jaśmina Joanna (Medycyna Paliatywna/Palliative Medicine, 2025)
Bereavement support, as a form of family assistance, is an integral component of palliative care. Because the grieving process can sometimes become prolonged and dysfunctional, disrupting the daily functioning of mourners and potentially developing into prolonged grief disorder (PGD), it is worth exploring the latest tools to support the grieving process. Rapidly advancing artificial intelligence (AI) is an example of modern technology that has found numerous applications in predicting, diagnosing, treating, and supporting individuals coping with the loss of a loved one. A quasi-systematic review was conducted by searching the PubMed and Scopus databases using specific MeSH terms. A total of 12 sources were included in the review. The literature used AI for conversational agents and deepfake technology (n = 6), prediction models (n = 3), identification of factors correlating with grief severity (n = 1), clustering grief and major depressive disorder (n = 1), and personalised assignment to an adequate therapy (n = 1). Most of the analysed techniques achieved good performance rates; however, conversational agents and deepfake technology have raised serious ethical and legal concerns. AI in bereavement support is mainly used for interactive deepfake technologies; however, this field should be thoroughly examined before its widespread implementation. A potentially valuable future application of AI in the grieving process lies in identifying individuals at increased risk of PGD, facilitating their diagnosis, and tailoring personalized therapeutic interventions for bereaved individuals. Under appropriate legal oversight and the supervision of a human therapist, these tools could be extremely helpful.